10 lat negocjacji akcesyjnych Turcji z Unią Europejską. Analiza postępów w obszarze kryteriów politycznych na podstawie raportów Komisji Europejskiej - Osiewicz, Przemysław (Rocznik Integracji Europejskiej, 2015)
October 2015 marked the tenth anniversary of the official onset of the accession negotiations between Turkey and the European Union. The outcome of the talks, however, has so far been more than modest. The negotiations have encompassed fourteen out of 35 fields, leading to the closure, albeit only preliminary, of only one field. Croatia started negotiations in the same year and has been EU member state for two years now. In the Turkish case, the end of the talks is nowhere to be seen, and the more time goes by the less likely it seems for Turkey to become a legitimate participant of a European integration process. The EU Commission continues to present a number of reservations as concerns the progress of Turkey on its path to accession. The aim of this paper is to attempt to find an answer to the question whether the catalogue of reservations brought up by the EU Commission in terms of the political criteria to be met by Turkey has changed after the nine years of negotiations. By this token it will become possible to determine the progress Turkey has made as concerns those political criteria, both quantitatively and qualitatively.